TUNA BAITFISH AND THE POLE-AND-LINE FISHERY IN NASTERN INDONESIA - AN OVERVIEW - Nurzali Naamin; Bachtiar Gafa (Research Center for Fisheries, 1998)
Skipjack tuna is the principal species in the pole-and-line fishery in the eastern part of Indonesia.